Practical teaching. Senses, tensions, alternatives (Praxis Educativa, 2021)
The article that we present belongs to the production of the UBACYT Project: "The teaching residence: senses of training based on clinical studies of residents in training devices" and is aimed at communicating some conceptualizations built from the in-depth knowledge of residency cases that we have been carrying out in our program and to think about training from new angles. Secondly, we will work on a problem found around the entrance to the residence through training proposals collected in the investigation and other open ones to provide tools in the construction of roads with transformative responses. We will take some conceptualizations that emerge from the study and that mean reformulations that we consider of interest to make known. These theoretical advances are hypothetical in nature and come from qualitative studies of singular cases that have allowed a greater understanding of the problem stated for this project, not a generalization. We will make proposals for changes to the residence consistent with what has been analyzed in the cases.
Keywords: research; teaching training; practical teaching; proposals